Four Newly Discovered Churches in Bithynia - Çetinkaya, Halûk (Actual Problems of Theory and History of Art, 2019)
During restorations held in Nicaea/İznik and Prusa ad Olympum/Bursa four new churches were discovered. Since restoration work did not aim at excavating the accidentally discovered churches this article intends to shed light by making use of the material available. Three of the churches were from Nicaea, two of which by the main gates of the city walls and the third one in the area next to the museum building of İznik. The church discovered in Bursa is located next to the city walls. Despite its unfinished excavation it has revealed immense material including the ambo with an inscription. The aim of this article is to contribute to the database of Byzantine monuments.